Effect of grain size refinement on microstructure and mechanical properties of AZ31 magnesium alloy. Issue 3 (April 2021) - Wang, Xin; Li, Mingda; Ma, Songyuan; Zang, Ji; Li, Dongping
Abstract: In this paper, microstructure and mechanical properties of ultra-grain size and coarse-grain size bulk AZ31 magnesium alloy were evaluated using tensile testing. The ultra-grain size (200nm) bulk AZ31 magnesium alloy showed well mechanical properties with stronger tensile strength (315MPa), typical ductile fracture surface and deep dimples, which can be attributed to grain size refinement of bulk AZ31 magnesium alloy.